Green Innovation, Environmental Management Accounting, and Environmental Performance: Their Impact on Firm Value - Azizah, Zelfi Nur; Wijayanti, Risna (Jurnal Management Risiko dan Keuangan, 2025)
Purpose – This study aims to analyze the relationships between green innovation, Environmental Management Accounting (EMA), and firm value, with environmental performance as a mediating variable.   Design/methodology/approach –  This research uses a quantitative approach with purposive sampling. The sample consists of 38 energy-sector companies listed on the Indonesia Stock Exchange during 2019–2022. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to examine direct and indirect relationships among variables.   Findings – The results show that green innovation and EMA significantly affect firm performance. Green innovation also has a significant effect on environmental performance. However, environmental performance does not mediate the relationship between green innovation, EMA, and firm value.   Originality/value – This study contributes to sustainability and corporate finance literature by providing evidence that environmental performance does not necessarily act as a mediating mechanism in linking green practices to firm value in the energy sector.